Technology of Welding and Joining - Węgrzyn, Tomasz (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, you will find information on new materials and new welding technologies. Problems related to the welding of difficult-to-weld materials are considered and solved. The latest welding technologies and processes are presented. This book provides an opportunity to learn about the latest trends and developments in the welding industry. Enjoy reading.